Compartmentalized Cyclic AMP Production by the Bordetella pertussis and Bacillus anthracis Adenylate Cyclase Toxins Differentially Affects the Immune Synapse in T Lymphocytes - Arumugham, Vijay B.; Ulivieri, Cristina; Onnis, Anna; Finetti, Francesca; Tonello, Fiorella; Ladant, Daniel; Baldari, Cosima T. (Frontiers in Immunology, 2018)
A central feature of the immune synapse (IS) is the tight compartmentalization of membrane receptors and signaling mediators that is functional for its ability to coordinate T cell activation. Second messengers centrally implicated in this process, such as Ca2+ and diacyl glycerol, also undergo compartmentalization at the IS. Current evidence suggests a more complex scenario for cAMP, which acts both as positive and as negative regulator of T-cell antigen receptor (TCR) signaling and which, as such, must be subjected to a tight spatiotemporal control to allow for signaling at the IS. Here we have used two bacterial adenylate cyclase toxins that produce cAMP at different subcellular localizations as the result of their distinct routes of cell invasion, namely B. pertussis CyaA and B. anthracis edema toxin (ET), to address the ability of the T cell to confine cAMP to the site of production and to address the impact of compartmentalized cAMP production on IS assembly and function. We show that CyaA, which produces cAMP close to the synaptic membrane, affects IS stability by modulating not only the distribution of LFA-1 and its partners talin and L-plastin, as previously partly reported, but also by promoting the sustained synaptic accumulation of the A-kinase adaptor protein ezrin and PKA while suppressing the β-arrestin mediated recruitment of phosphodiesterase 4B. These effects are dependent on the catalytic activity of the toxin and can be reproduced by treatment with a non-hydrolysable cAMP analogue. Remarkably, none of these effects are elicited by ET, which produces cAMP at a perinuclear localization, despite its ability to suppress TCR signaling and T cell activation through its cAMP-elevating activity. These results show that the IS responds solely to local elevations of cAMP and provide evidence that potent compartmentalization mechanisms are operational in T cells to contain cAMP close to the site of production, even when produced at supraphysiological levels.